Kewenangan Daerah Otonom Dalam Menjalankan Fungsi Pemerintahan Di Indonesia - Sarkawi - (Jatiswara, 2015)
The purpose of writing this article is to determine the autonomous regional authority in carrying out the functions of government in Indonesia . Results and conclusions in this paper is the autonomous regional authority in carrying out the functions of government in Indonesia is in the form of government affairs concurrent authority regulated in Law Number 23 Year 2014 concerning regional governments. The concurrent administration affairs consisting of Government Affairs and Government Affairs Mandatory options. Mandatory Government Affairs consisting of Government Affairs with regard to Basic Services and Government Affairs that are not related to the Basic Service. While the Mandatory Government Affairs relating to Basic Services are partially Mandatory Government Affairs substance is a Basic Service .